Analisis Voltage Drop Pada Jaringan Tegangan Rendah Dengan Metode Pecah Beba Pada Gardu KH 007 Di PT PLN (Persero) UP3 Pamekasan - Ibnu Hajar; Nurmiati Pasra; Denny Rusmansyah (Sekolah Tinggi Teknik - PLN, 2020)
In the operation of the electric power system, good quality service is needed. One of them is thevoltage value received by the customer does not get a voltage drop. Based on SPLN No.1: 1978, theservice voltage is a maximum of 5% and a minimum of 10% of the nominal voltage of the LowVoltage Network that is 220 Volt. One of the locations experiencing voltage drop problems is on theCentral Pakandangan Village, Sumenep. Based on an analysis do by the PT PLN UP3 PamekasanNetwork division, it turns out that the voltage drop that occurred on Central Pakandangan Villagecaused by the location. The location is to far from the KH 007 distribution substation, which is 643meters. Then, the area around the location also has a high burden due to the many standingresidential settlements. Therefore, it is necessary to break the load on the network. This method isdone by moving or transferring part of the load from the old network to the new network. Which isthe last 5 poles in this line. so the load supported by one line does not have voltage drop. The resultobtained after performing the load break is that the voltage on the receiving side rises to phase R200 Volt, phase S 212 Volt, and phase T 202 Volt. Where previously the value of the voltage on thereceiving side is phase R 189 Volt, phase S 206 Volt, and phase T 194 Volt.